The Effect Of Using Social Media On The Students’ Vocabulary Achievement At Tenth Grade Students Of SMA Swasta Persiapan Stabat Academic Year 2017/2018 - Ayu Indari; Maydita Mulia Cahyani Putri (JURNAL TARBIYAH, 2018)
The study is aimed at finding out the effect of social media on students’ vocabulary achievement. The writers choose the 2017/2018 tenth year students of SMA Swasta Persiapan Stabat as the subjects of the study. The population of the 2017/2018 tenth year students was 244 students. The writers took classes, namely X IPA-4 with 40 students and X IPS-2 with 35 students as the sample of the study and they were divided into experimental and control groups. The experimental group was taught by applying social media, while the control group was taught without social media. The data got from pre-test and posttest was analyzed by using t-test. The result of the t-test showed that the value of t observed was 9, 34. The t observed value of 9, 34 was higher than the value of t-table 2, 00 and 2, 66. This indicated that alternative hypothesis (Ha) was accepted. Therefore, the result of the study showed that there is significant effect of social media on students’ vocabulary achievement of the 2017/2018 tenth year students of SMA Swasta Persiapan Stabat.